Association of AST/ALT ratio with 90-day outcomes in patients with acute exacerbation of chronic liver disease: a prospective multicenter cohort study in China - Liu, Huimin; Li, Hai; Deng, Guohong; Zheng, Xin; Huang, Yan; Chen, Jinjun; Meng, Zhongji; Gao, Yanhang; Qian, Zhiping; Liu, Feng; Lu, Xiaobo; Shi, Yu; et al. (Frontiers in Medicine, 2024)
Background and Aim: A high aspartate aminotransferase/alanine aminotransferase (AST/ALT) ratio is associated with liver injury in liver disease; however, no data exist regarding its relationship with 90-day prognosis in patients with acute exacerbation of chronic liver disease. Methods In this study, 3758 participants (955 with advanced fibrosis and 2803 with cirrhosis) from the CATCH-LIFE cohort in China were included. The relationships between different AST/ALT ratios and the risk of adverse 90-day outcomes (death or liver transplantation) were determined in patients with cirrhosis or hepatitis B virus (HBV)-associated advanced fibrosis, respectively. Results In the patients with HBV-associated advanced fibrosis, the risk of 90-day adverse outcomes increased with AST/ALT ratio; after adjusting for all confounding factors, the risk of adverse 90-day outcomes was the highest when AST/ALT ratio was more than 1.08 (OR=6.91 [95% CI=1.789–26.721], P=0.005), and the AST/ALT ratio of >1.9 accelerated the development of adverse outcomes. In patients with cirrhosis, an AST/ALT ratio >1.38 increased the risk of adverse 90-day outcomes in all univariables (OR=1.551 [95% CI=1.216–1.983], P<0.001) and multivariable-adjusted analyses (OR=1.847 [95% CI=1.361–2.514], P<0.001), and an elevated AST/ALT ratio (<2.65) accelerated the incidence of 90-day adverse outcomes. An AST/ALT ratio of >1.38 corresponded with a more than 20% incidence of adverse outcomes in patients with cirrhosis. Conclusions The AST/ALT ratio is an independent risk factor for adverse 90-day outcomes in patients with cirrhosis and HBV-associated advanced fibrosis. The cutoff values of the AST/ALT ratio could help clinicians monitor the condition of patients when making clinical decisions.